Personality of Ibn e Kathir and His Methodology in Al-Sīrah Al-Nabawiyyah - Al Azhari, Muhammad Riaz Khan; Muhammad Waqas, (Journal of Islamic and Religious Studies, 2018)
Sīrah is the topic which started during 1st Hijrah, from that time till now there are several books written on this topic, there is no such personality in history other than Prophet Muhammad (PBUH) whose biography from his birth till his death is preserved in such a manner. None of the aspect of his life is hidden, there was no such personality in history that was praised to such an extent. There are so many books written on the Sīrah of Holy Prophet (PBUH), but the one which was written by Allama Ibn-e-Kathir is indeed unique among them all. During his era there were too many books written on Sīrah al-Nabawiyyah but his command on Ḥadith and Fiqh made his work unique among others, he added authentic Aḥadith and narrations in his book and included such points which remained hidden from other authors. His book consists of 4 parts, and also includes Fiqh al Sīrah, which shows his great command over Fiqh (Islamic Jurisprudence). The work of Ibn-e-Kathir helps in deeply understanding the Sīrah of Prophet.